Experimental Study on the Comparative Flexural Strength of Reinforced Concrete Beams under Post-Burning Conditions at 350°C, 450°C, and 550°C - Samsul Abdul Rahman Sidik Hasibuan (Universitas Medan Area, 2024)
Reinforced concrete is widely used in structural engineering due to its high compressive strength, durability, and cost efficiency. However, its mechanical performance significantly deteriorates when exposed to elevated temperatures such as fire, leading to moisture evaporation, microcracking, and decomposition of calcium silicate hydrate (C–S–H). This study aims to analyze and compare the flexural strength of reinforced concrete beams subjected to post-burning conditions at 350°C, 450°C, and 550°C, and to evaluate the degradation trend as temperature increases. An experimental laboratory approach was employed using reinforced concrete beam specimens with identical geometry and material properties. The specimens were exposed to controlled furnace heating for 30 minutes at each temperature level, followed by natural cooling before testing. Flexural strength was determined using a two-point loading system in a Universal Testing Machine. The results show a continuous reduction in flexural strength with increasing temperature, where the control specimen recorded 27.556 MPa, while specimens exposed to 350°C, 450°C, and 550°C showed strengths of 25.81 MPa, 24.01 MPa, and 21.697 MPa, respectively. The relationship between temperature and flexural strength demonstrates an excellent correlation with an R² value of 0.9952, indicating a highly predictable degradation pattern. The reduction is attributed to progressive microstructural damage, decomposition of hydration products, and weakening of the interfacial transition zone between concrete and reinforcement. The findings confirm that temperatures above 500°C cause significant structural deterioration. It is recommended that fire-damaged concrete structures undergo detailed post-fire assessment prior to reuse. The results provide important implications for structural fire safety design and rehabilitation strategies for reinforced concrete structures.